Azithromycin and ciprofloxacin resistance in Salmonella bloodstream infections in Cambodian adults. - Erika R Vlieghe; Thong Phe; Birgit De Smet; Chhun H Veng; Chun Kham; Sophie Bertrand; Raymond Vanhoof; Lut Lynen; Willy E Peetermans; Jan A Jacobs (PLoS Neglected Tropical Diseases)
Background Salmonella enterica is a frequent cause of bloodstream infection (BSI) in Asia but few data are available from Cambodia. We describe Salmonella BSI isolates recovered from patients presenting at Sihanouk Hospital Centre of Hope, Phnom Penh, Cambodia (July 2007-December 2010). Methodology Blood was cultured as part of a microbiological prospective surveillance study. Identification of Salmonella isolates was performed by conventional methods and serotyping. Antibiotic susceptibilities were assessed using disk diffusion, MicroScan and E-test macromethod. Clonal relationships were assessed by Pulsed Field Gel Electrophoresis; PCR and sequencing for detection of mutations in Gyrase and Topoisomerase IV and presence of qnr genes. Principal findings Seventy-two Salmonella isolates grew from 58 patients (mean age 34.2 years, range 8-71). Twenty isolates were identified as Salmonella Typhi, 2 as Salmonella Paratyphi A, 37 as Salmonella Choleraesuis and 13 as other non-typhoid Salmonella spp. Infection with human immunodeficiency virus (HIV) was present in 21 of 24 (87.5%) patients with S. Choleraesuis BSI. Five patients (8.7%) had at least one recurrent infection, all with S. Choleraesuis; five patients died. Overall, multi drug resistance (i.e., co-resistance to ampicillin, sulphamethoxazole-trimethoprim and chloramphenicol) was high (42/59 isolates, 71.2%). S. Typhi displayed high rates of decreased ciprofloxacin susceptibility (18/20 isolates, 90.0%), while azithromycin resistance was very common in S. Choleraesuis (17/24 isolates, 70.8%). Two S. Choleraesuis isolates were extended spectrum beta-lactamase producer. Conclusions and significance Resistance rates in Salmonella spp. in Cambodia are alarming, in particular for azithromycin and ciprofloxacin. This warrants nationwide surveillance and revision of treatment guidelines.